2011
DOI: 10.1088/0957-4484/22/11/115602
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of surface magnetic nanoclusters using low energy ion implantation and electron beam annealing

Abstract: Magnetic nanoclusters have novel applications as magnetic sensors, spintronic and biomedical devices, as well as applications in more traditional materials such as high-density magnetic storage media and high performance permanent magnets. We describe a new synthesis protocol which combines the advantages of ion implantation and electron beam annealing (EBA) to produce surface iron nanoclusters. We compare the structure, composition and magnetic properties of iron nanoclusters fabricated by low dose 15 keV Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…40 keV Er ions were implanted into polycrystalline ZnO thin films using GNS low-energy ion implanter [9]. The ZnO films were prepared using ion beam sputtering system with a thickness around 150 nm [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 keV Er ions were implanted into polycrystalline ZnO thin films using GNS low-energy ion implanter [9]. The ZnO films were prepared using ion beam sputtering system with a thickness around 150 nm [10].…”
Section: Methodsmentioning
confidence: 99%
“…Here onwards, the samples annealed in high vacuum and air atmosphere are labeled as ''HVA 650°C'' and ''Oxy 650°C'', respectively. Rutherford backscattering spectrometry (RBS) measurements were conducted using a 1 mm collimated 2 MeV 4 He + beam [9,12]. The backscattered particles were collected using a Si surface barrier detector placed at a scattering angle of 165°.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication methods are still being actively developed. Recently, Kennedy et al demonstrated a method for depositing magnetic nanoclusters surface using ion implantation on dielectric SiO 2 followed by electron beam annealing at 1000°C [65]. The nanoclusters with particles ranging from 5 to 40 nm were obtained.…”
Section: Multiplexed Molecular Sensingmentioning
confidence: 99%
“…The various conventional methods to synthesise nanoparticles include chemical synthesis [5], polyol synthesis [6], laser ablation [7], and arc discharge [8]. Ion implantation is a novel method that could potentially be used to synthesise magnetic nanoparticles with unique properties tailored to suit different applications [9][10][11]. Near-surface iron nanoparticles have previously been synthesised in SiO 2 films using low-energy ion implantation followed by electron beam annealing [9,10].…”
Section: Introductionmentioning
confidence: 99%